Doping-induced stability in vanadium-doped ZnO quantum well wires (QWW): Combination of DFT calculations within experimental measurements - YUMAK YAHŞİ, AYŞE (ELSEVIER, 2016)
ZnO quantum well wires (QWW) have grown on glass substrates by an inexpensive, simplified and enhanced spray pyrolysis technique then doped by Vanadium. The effects of V-doping on the structural, morphological and optical properties of the QWW were investigated experimentally and theoretically. The accuracy of control can be achieved on functional performance by adjusting vanadium doping extent. The incorporation of Vanadium in ZnO-QWW induced the formation of band tailing in states. The interactions with phonons and the presence of a tail absorption profile are following the empirical Urbach law. The electronic structure using density functional theory have shown the changes induced by vanadium doping in ZnO-QWW, where the phonon band structure and density of states were reported. The DFT results showed a good agreement with the lattice compatibility theory as well as with the experimental results. (C) 2016 Elsevier Masson SAS. All rights reserved.
Keywords: ZnO; Vanadium; Doped thin films; Quantum well wires; Morphology; Optical properties; Vibrational properties and phonons; TOTAL-ENERGY CALCULATIONS; OPTICAL-PROPERTIES; THIN-FILMS; MICROSTRUCTURE